2016
DOI: 10.1186/s12954-016-0116-z
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful engagement of people living with HIV who use drugs: methodology for the design of a Peer Research Associate (PRA) hiring model

Abstract: BackgroundCommunity-based HIV, harm reduction, and addiction research increasingly involve members of affected communities as Peer Research Associates (PRAs)—individuals with common experiences to the participant population (e.g. people who use drugs, people living with HIV [PLHIV]). However, there is a paucity of literature detailing the operationalization of PRA hiring and thus limited understanding regarding how affected communities can be meaningfully involved through low-barrier engagement in paid positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Previous research has identified key challenges to PRA training within the context of a CBR study, including limited financial resources and a significant time commitment required to sustainably support trainees [43, 51, 52]. We were fortunate to learn from this work to develop and implement a PRA hiring and training process.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has identified key challenges to PRA training within the context of a CBR study, including limited financial resources and a significant time commitment required to sustainably support trainees [43, 51, 52]. We were fortunate to learn from this work to develop and implement a PRA hiring and training process.…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has identified good practice methods to the meaningful involvement of PWUD in policy, health services, and research (such as [1, 8, 19, 3942]). However, much of this literature has focused on good practice engagement strategies and their benefits, with much less emphasis on the system level factors that may enhance or constrain meaningful involvement [6, 13].…”
Section: Results: Learnings On the Involvement Of Pwud Peer Organizatmentioning
confidence: 99%
“…Enhancing the meaningful involvement of PWUD and their peer organizations in research and policy has been an ongoing endeavor for decades [1] with literature discussing good practice as well as barriers and enablers [8, 25, 3942, 52]. However much of this literature has focused on engagement strategies and research methodology, with much less emphasis on identifying system level factors that may enhance or constrain meaningful involvement [6, 13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although traditional methods facilitate inferential statistics on the larger population from which the sample is drawn, there are many limitations of the methods that have raised a lot of discussion in the academic community (Broadhead, 2008; Lansky & Mastro, 2008; Ouellet, 2008; Scott, 2008). For example, there have been concerns related to tokenistic involvement of marginalized participants and associated underground economy, risk of violence, coercion, or false reporting (Closson et al, 2016; Logie, James, Tharao, & Loutfy, 2012; Richardson, Wood, & Kerr, 2013; Scott, 2008).…”
Section: Literaturementioning
confidence: 99%
“…Since the main successive component of the traditional social network methodology’s sampling strategy has been focused on “peers” or “seeds,” mainly based on the notion that such individuals are better able to locate and access the hard-to-reach populations than outreach workers or experienced researchers, we believe that better outcomes can be achieved if peers or people with lived or current experiences of illegal drug use not only act as a referral point but also be invited to partake in the research design, implementations, data collection, data entry, and dissemination of findings in the community (Brizay et al, 2015; Greene, 2013; Jagosh et al, 2012; Wright, 2015). In fact, there is growing interest by health researchers to give greater roles to people affected by the health problems under study (Boyd, 2013; Boyd, Murray, & MacPherson, 2017; Closson et al, 2016; Cropper et al, 2010; Greer et al, 2016; Wright, 2015).…”
Section: Literaturementioning
confidence: 99%